2012
DOI: 10.1364/oe.20.022475
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in the momentum distributions of electrons stripped by a XUV chirped pulse in the presence of a laser field

Abstract: The ionization of hydrogen by a chirped XUV pulse in the presence of a few cycle infrared laser pulse has been investigated. The electron momentum distribution has been obtained by treating the interaction of the atom with the XUV radiation at the first order of the time-dependent perturbation theory and describing the emitted electron through the Coulomb-Volkov wavefunction. The results of the calculations agree with the ones found by solving numerically the time-dependent Schrödinger equation. It has been fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…However, along with gaining a basic understanding of a process it is always important to devise schemes to control the outcome of a process so that it can be put to significant uses. Recently schemes have been proposed where x-ray/x-uv attosecond laser sources are chirped to investigate different field induced processes like ionization [23,24], stimulated resonant inelastic scattering [25], RA [26] etc. One such recent work has reported that chirping of a free electron laser can induce suppression of the RA process in the course of pulse propagation [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, along with gaining a basic understanding of a process it is always important to devise schemes to control the outcome of a process so that it can be put to significant uses. Recently schemes have been proposed where x-ray/x-uv attosecond laser sources are chirped to investigate different field induced processes like ionization [23,24], stimulated resonant inelastic scattering [25], RA [26] etc. One such recent work has reported that chirping of a free electron laser can induce suppression of the RA process in the course of pulse propagation [26].…”
Section: Introductionmentioning
confidence: 99%